SISTEM PENGETAHUAN MASYARAKAT SELUMA DALAM PEMANFAATAN TANAMAN OBAT TRADISIONAL - Ardian Alek Sono; Otoman; Fitriah (Tanjak: Sejarah dan Peradaban Islam, 2025)
This study describes the local knowledge of the community regarding the types of medicinal plants in Talang Padang Village, Talo Kecil District, Seluma Regency using a qualitative approach. The main framework for thinking about this problem includes: [1] Local knowledge of the community in Talang Padang Village regarding the types of traditional medicinal plants. [2] Utilization and processing of types of traditional medicinal plants found in Talang Padang Village. The study used in this study is an anthropological study using a scientific approach and a local approach that focuses on the local knowledge and culture of the community in Talang Padang Village regarding the types of traditional medicinal plants. The methods used for data collection are observation methods, limited interviews, documentation, and literature studies. Data analysis is processed descriptively qualitatively and compiled using an inductive method. In this study, the data sources used are primary sources obtained from shamans, local communities and local government. And the secondary data comes from the archives of the village government bookkeeping related to this study. The results of the study obtained that the community in Talang Padang Village knows traditional medicine using wild plants, both those found around the yard and those growing wild in the forest, obtained from the ancestors in Talang Padang Village, where the concoction and processing of these types of medicinal plants are inherited to children or students from the ancestors of the Talang Padang Village community. Then from this study, it was also found that the mantra used by the shaman in treating a disease, the mantra is used when treating the disease experienced by the community when they come for treatment. This type of treatment is still widely practiced and is still very much believed in by the people of Talang Padang Village.